Modifying the "Eye of the Tiger" Technique: Preserving Gluteal Artery Perfusion in the Treatment of an Aneurysm of the Hypogastric Artery. (April 2021) - Iwakoshi, Shinichi; Inagaki, Masahiro; Yoshiyama, Yutaka; Shimohara, Yuichi; Yamashita, Masanori; Ichihashi, Shigeo; Kichikawa, Kimihiko
Purpose: In endovascular aneurysm repair, parallel stent graft deployment is sometimes utilized to preserve the distal branch perfusion. However, there will be some gutter space around 2 stent grafts, which may cause endoleak. The "eye of the tiger" technique was invented to minimize this leak when deploying a small side-branch stent graft in conjunction with a large aortic endograft. The purpose of this case report is to describe our modified technique for 2 small endografts deployed in double D-shape in order to prevent gutter leak, which we applied in endovascular treatment for a hypogastric artery aneurysm. Case Report: A 79-year-old male patient presented with a right hypogastric artery aneurysm measuring 44 mm. The patient refused the open surgical repair option and hoped for an endovascular treatment. Therefore, endovascular treatment to exclude the hypogastric artery aneurysm as well as preserve the gluteal arteries was planned. An Internal Iliac Component (IIC)(W. L. Gore & Associates, Flagstaff, AZ, USA) was utilized for the proximal sealing and 2 Viabahn stent grafts (W. L. Gore & Associates) were deployed in the superior and inferior gluteal arteries for distal sealing. Then, 2 VBX stent grafts (W. L. Gore & Associates) were added in the IIC as bridging stents to connect the IIC and both Viabahn stent grafts. Next, over-dilatation of VBX stent grafts was performed alternately with an 8 mm balloon catheter and subsequent kissing balloon dilation with 5 mm balloon catheters, which allowed the VBX stents to be set in double D-shape. A follow-up CT scan performed 1 week after the procedure revealed no endoleak and a favorable shape to the VBX stent grafts. Conclusion: The modified method of dilating the VBX stent grafts allowed the double D-shape deployment, minimizing the risk of gutter leak and preserving distal branch perfusion.